Transnationalism in Joshi’s Shramatan - Kattel, Achut Raj (Medha: A Multidisciplinary Journal, 2024)
This article analyses how Bn Joshi’s nonfiction Shramatan presents the life of people in Gulf countries. The study is essential to understand about Nepali youths’ involvement in foreign employment and changes they have in themselves after they return the homeland from host land. This article inquires what compels Nepali youths to leave the country and how they get changes in themselves after transnational migration. The major objectives of the study are to trace the causes of transnational migration of Nepali youths, show the relationship between homeland and host land and record the various transformations that result from the transnational migration in the lives of migrants. The theoretical perspective on transnationalism by Levitt, Jaworsky, Vertovec and Faist and Fauser is the basis of research in the article. The major finding is that transnational migration results in economic, political, social, cultural and psychological transformation in the life of migrants. The study concludes that lack of opportunity is the major cause of transnational migration and transnationalism transforms the migrants’ life internally and externally. Similarly, transnational migrants develop some relationship with the society of host land. Further research is essential on this nonfiction that from the point of view of diaspora.